Analisis Faktor-Faktor Yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan - Larasati, Alda; Kencana, Dwi Tirta; Sihono, Shiwi Angelica Cindiyasari (Politeknik Negeri Ambon, 2024)
This research aims to determine the influence of company size, profitability, company age, and audit opinion on financial reporting time criteria. This research is a quantitative descriptive study that aims to assess the performance of a food and beverage sub-sector company listed on the IDX. The timeliness of financial reporting is measured using company size, profitability, company age, and audit opinion. The object of this research is food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling method used in the collection was a purposive sampling method with data collection techniques in the form of documentation, based on established criteria, a sample of 37 companies was obtained. The research period used is 2020-2022. , the operational definition of the variable is divided into two variables, namely the independent variable and the dependent variable using panel data analysis techniques using Eviews version 10 software. The research results show that the variables company size, profitability, and company age have a negative effect, and audit opinion has a positive effect on financial reporting time performance.